Precision nitrogen, irrigation and cultivation regimes for enhanced yield, and nutrient accumulation in direct-seeded basmati rice (Oryza sativa) - PRATAP, VIJAY; DASS, ANCHAL; DHAR, SHIVA; KUMARI, KAVITA; SUDHISHRI, S (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during rainy (kharif) seasons of 2019 and 2020 at ICAR-Indian Agricultural Research Institute, New Delhi to monitor the effect of precision nitrogen (N) and water management options on yield and nutrient acquisition in grain and straw of direct-seeded rice (DSR, basmati) (Oryza sativa L.). Experiment was conducted under two cultivation methods, in a triplicate split-plot design (SPD). The main-plots were allocated to 6 combinations of 2 DSR cultivation approaches, viz. growing DSR in ploughed land (CTDSR); and growing DSR without tilling the land (ZTDSR); and 3 water regimes [adequate water; water supply at 20% available soil moisture exhaustion (ASME); and 40% ASME + silicon (Si) supply @80 kg/ha]. Sub-plots had 3 N supply decisions, viz. 100% recommended rate of N (RRN: 150 kg/ha); NutrientExpert (NE) + leaf colour chart (LCC); and NE + soil plant analysis development (SPAD) meter-based N scheduling. Conventional till-direct seeded rice produced 1.9, 3.1 and 5.7% greater grain yield, grain protein content and protein yield, respectively, over ZTDSR; the respective improvement in grain N, P and K uptake was 5.9, 7.9 and 4.9%. Adequate water regime resulted in 11.5, 7.3 and 18.7% more grain yield, grain protein content and protein yield, respectively, over water supply at 20% ASME with concomitant enhancement in grain N, P and K uptake of 19, 24 and 23%, respectively. A significant improvement in grain yield (9.2%), grain protein (11.7%) content and protein yield (22.1%) was detected with NE® + SPAD meter- based N application over RRN; the N, P and K uptake in grain also spiked by 22.1, 42.1 and 31.7%, respectively. Hence, NE + SPAD-based N application and adequate water regime (irrigation at 72 h of drying of surface water) could be beneficial for improving yield and quality of both CA-based and conventionally cultivated DSR.